2011
DOI: 10.3109/00365599.2011.552436
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of fibroblast growth factor receptors FGFR1 and FGFR2 in renal cell carcinoma

Abstract: This study has shown for the first time that FGFR1 is highly expressed in RCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37). FGFR also is involved in autocrine activation of STAT3 as a positive feedback in many drug-treated cancer cells which are driven by diverse oncogenes such as EGFR, ALK, MET, and KRAS (38).…”
Section: Significancementioning
confidence: 99%
“…Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37). FGFR also is involved in autocrine activation of STAT3 as a positive feedback in many drug-treated cancer cells which are driven by diverse oncogenes such as EGFR, ALK, MET, and KRAS (38).…”
Section: Significancementioning
confidence: 99%
“…Other than this, overexpression of FGFR1 and FGFR2 has been reported in renal cell carcinoma [110]. FGFR2 is overexpressed in breast cancer and gastric cancer [111,112]. Human myeloid cells, bladder carcinoma as well as urinary tract carcinomas overexpress FGFR3 [113][114][115].…”
Section: Fgf and Fgfrs: Roles In Cancermentioning
confidence: 99%
“…The level of FGFR expression was compared with 40 specimens of normal human kidney tissue (selected from the surgical diagnostic files) [15]. FGFR1 expression was identified in 98% of the cases in primary renal tumor cells and in 82.5% of the cases in lymph node metastases.…”
Section: Importance Of the Fgf/fgfr Pathway In Rcc Pathogenesismentioning
confidence: 99%